Influencia del combustible en la eficiencia de una máquina térmica: estudio de caso de un motor de combustión mono cilíndrico (2023)
The main objective of this research is to verify the influence of fuel on the efficiency of a thermal machine, an engine located at the Antonio Nariño University headquarters in Puerto Colombia.